2(6x+1)=(x-5)-2

Simple and best practice solution for 2(6x+1)=(x-5)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6x+1)=(x-5)-2 equation:


2(6x+1)=(x-5)-2

We simplify the equation to the form, which is simple to understand
2(6x+1)=(x-5)-2

Reorder the terms in parentheses
+(+12x+2)=(x-5)-2

Remove unnecessary parentheses
+12x+2=+(+x-5+)-2

Remove unnecessary parentheses
+12x+2=x-5-2

We move all terms containing x to the left and all other terms to the right.
+12x-1x=-5-2-2

We simplify left and right side of the equation.
+11x=-9

We divide both sides of the equation by 11 to get x.
x=-0.818181818182

See similar equations:

| 2p=-3p-6-4 | | 1-5x=-2(x+4) | | -5t-3-t+8=2t-7 | | 7(x-2)=5(+2) | | 21nx+2=5 | | x^2+32x+100=0 | | z^2-3=11z/2 | | (X*220)/1000 | | 5n-2=0 | | 3x^2+3x+x^3=-1 | | 3x^2+3x-x^3=-1 | | 3(2x+-1)=39 | | 3x^2-3x-x^3=-1 | | n^2+5n=12 | | 1000=x+x*0.28 | | (5y^2-2y+6)-(-5y^2+8y-7)+(-4y^2+3y-3)= | | 5x+3=3x-6 | | -5(r+3)=-79 | | 5r-10=15 | | ln(7x)/(3) | | v-5(v-20)=0 | | b-3+4b=21 | | 20b+2(6b-1)=34 | | w^5*w*w^3= | | 1000=x*0.208+x*0.005+x | | 5y^2-6y+22=30 | | 1000=x*0.208+x*0.005 | | 8b-7=7b-s | | 5x+12=-20 | | 5+-1=7t-5 | | 2p^2+6p-5=0 | | 6(x+4)=8x+5-2x+19 |

Equations solver categories